Financial literacy, network competency, market orientation and financial performance: A study from Bandung SMEs - Raynald Phoebus Mihardjo; Mega Noerman Ningtyas (Diponegoro International Journal of Business, 2023)
Indonesia SMEs have contributed 61.97% to GDP or Rp. 8,573.89 trillion, and they can absorb almost 97% of the workforce. However, several problems arise and become limitations for SMEs, such as limited capital and limited marketing ability and weak business management capabilities. For capital limitations, it can be solved by applying for credit to external parties such as banks and venture capital, but SMEs must meet the bank requirements. For marketing limitations, it can be pursued by maximizing the ability of SMES actors in network competence and market orientation. Therefore, this research was conducted to examine the financial literacy, network competence, and market orientation to the financial performance of SMEs. We collected data by an online questionnaire on 197 SMEs in Bandung. We use SEM PLS to analyze the data. Our results indicated that financial literacy, network competence, and market orientation had a positive and significant impact on the SMEs financial performance. That means that the ability to understand financial concepts, the ability to establish good relationships or networks with external parties, and the ability to sense markets and customer relations help SMEs to implement their business strategies properly. So that they will have an impact on increasing financial performance.